Культура в кризисном социуме и государственная поддержка народной культуры в Украине - Иванкова-Стецюк, О. (Социология: теория, методы, маркетинг, 2000)
The article is devoted to the folk cultureís socioregulating functions in the modern Ukraine socium and to the regarding its functions as a sociocultural system in thefuture. The author is formulating the conception of the state support for the folkculture. The conception includes the offers related to the self-correction processes inthe realm of this kind of culture. The versions of sociological analysis of the folk artworks are proposed in this context. The version of the model of how artistic gifted youth is inculturated also presented. The author is using results of sociological investigations, which contain the information about situation in the artists education in Ukraine.